Issue Cover (April 2017). Issue 1 (April 2017) - Unknown
Abstract : Front cover: Low vacuum scanning electron micrograph of regenerating peripheral nerve. Visible with high contrast are lipid rich rings of Schwann cells remyelinating regenerated axons as well as macrophages that have surrounded degenerating fibres and phagocytosed myelin. Image taken by Mr Peter Bond in the Plymouth University Electron Microscopy Centre. The background to our study is to test the function of the p38 mitogen activated protein kinase pathway within Schwann cells of the PNS and how this pathway regulates the process of developmental myelination, as well as the loss of myelin proteins and functional repair following injury. Various studies have attempted this analysis previously using either chemical inhibitors of p38 activity or global genetic knockouts of p38 activity in all cells of the PNS, with some contradictory results. Ours is the first study to definitively test the role of p38 activity specifically in Schwann cells. We find that p38 activity in Schwann cells has an inhibitory effect on developmental myelination, nerves with loss of p38 in Schwann cells myelinate at an earlier developmental timepoint. In keeping with this function, we find that Schwann cells with reduced p38 activity down‐regulate myelin expression more slowly than controls following injury, but both axonal regeneration and functional repair are unchanged in nerves containing p38 null Schwann cells. These findings confirm a role for p38 activity in regulating myelination by Schwann cells, but the events of Wallerian degeneration, such as axonal breakdown, regrowth of axons and consequent functional recovery do not depend upon p38 function in Schwann cells. Read the full article ' The role of p38alpha in Schwann cells in regulating peripheral nerve myelination and repair ' by S. L. Roberts, X.‐p. Dun, G. Dee, B. Gray, T. Mindos and D. B. Parkinson ( J. Neurochem . 2017, vol. 141 (1), pp. 37–47) on doi:10.1111/jnc.13929